KAJIAN PROBLEM PEMBERIAN OBAT PADA PASIEN PEDIATRI RAWAT INAP DI RS PKU MUHAMMADIYAH YOGYAKARTA - , Zulfa Wahyundari, Prof. Dr. Lukman Hakim, M.Sc., Apt ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Background : Drug using for children is special case related to difference of organ development rate, body system and enzyme that responsible to metabolism and medicine excretion. Based on the research in New York, medication error on child inpatient in hospital increase three times to adult patient. Whereas research about drug administration problem to child patient in RS PKU Muhammadiyah Yogyakarta has never done. Purpose : The purpose of this research is to know the kind and percentage of drug administration problems to pediatric patient, and aslo the relationship between total incidence of drug administration problems and length of stay (LOS). Method : This research was conducted with an observational study design with prospective data collecting in pediatric patients. Population of this research is pediatric inpatients period from May to July 2010. Data obtained from medical record and interviews with patient and family, physician and nurse then analyzed descriptively to determine the type of drug administration problem that occur and the percentage of occurrence. Correlations analysis was used to define the relationship between total incidence of drug administration problems and length of stay (LOS). Result and Conclusions : Subjects who fulfilled the inclusion criteria of research conducted on May to July 2010 are 109 patients. From those 109 patient, there were 38 patients (34,86%) who experienced drug administration problem with incidence 60 events. Type of drug administration problem that occur are: inappropriate indication (8,47%), inappropriate drug selection (16,95%), inappropriate patient (5,08%), inappropriate dosage (8,47%), drug incompatibilities (5,08%), inappropriate of drug dosage selection (6,78%), inappropriate of drug administration frequencies (6,78%), inappropriate drug usage times (35,59%), and failure in receiving medication (6,78%). Furthermore, result of statistical analysis concluded that there was no relationship between total incidence of drug administration problems and length of stay (LOS).